Project under EPICS I2P Air Purifier for an Old Age Home - Sharma, Manisha; Kumar, Ajay; Bachhar, Abhishek; Unnisa, Azeem (Journal of Engineering Education Transformations, 2018)
The project is meant for an old age home as we worked under EPICS (Engineering Projects in Community Services) during our mini project by following EPICS design process. We identified community partner's need and accordingly we came up with "I2P Air Purifier". This air purifier is capable of monitoring and cleaning the air present in a room automatically, when the set limit exceeds as per doctor's prescription. I2P air purifier consists of two parts, one is monitoring part which displays temperature, humidity, LPG leakage, carbon content and other gases present in the air and gives indication whenever required about exceeded levels and other part is filter which consists of several layers through which air passes and gets purified. The device is portable and can be used anywhere.